1981
DOI: 10.2307/3280489
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Host Sex and Hormones on Trichinella spiralis in the Mouse

Abstract: The effects of host's sex and hormones on the number of adult Trichinella spiralis in the small intestine, the number of migratory larvae produced in vitro by adult female worms, and the number of muscle larvae per gram of body weight were examined in CD-1 Swiss white mice. Nongonadectomized (intact) male mice housed greater numbers of adult worms and a greater number of muscle larvae per gram of body weight than did intact female mice. Adult female worms isolated from intact male mice deposited greater number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…Disease prevalence was found to be more in males than in females. This is in accordance with the findings of [24,25]. The infection was again more in Sokoto Gudali than in Red Bororo breed and the White Fulani breed of cattle.…”
Section: Discussionsupporting
confidence: 81%
“…Disease prevalence was found to be more in males than in females. This is in accordance with the findings of [24,25]. The infection was again more in Sokoto Gudali than in Red Bororo breed and the White Fulani breed of cattle.…”
Section: Discussionsupporting
confidence: 81%
“…The experimentally elevated T levels in the male mice cause an increase in parasite intensity, as predicted under the T-induced immunosuppression paradigm. This is consistent with the results of Reddington et al (1981), who showed that gonadectomized female mice injected with T shed more T. spiralis muscle larvae than male mice. T-induced increases in susceptibility to infection have also been demonstrated in several host-parasite systems (e.g., Hughes and Randolph 2001;Mougeot et al 2006;Cox and John-Alder 2007).…”
Section: Discussionsupporting
confidence: 94%
“…Particularly on T. spiralis infections, it has been described a resistance/susceptibility associated to gender's host; in which males are more susceptible than females [22, 23]. Interestingly, in pregnant rats, where progesterone levels is increased, the resistance to T. spiralis infections throught parasite loads in muscle are increased compared to parasite loads in muscle observed in virgin rats.…”
Section: Discussionmentioning
confidence: 99%